Anifrolumab in the Treatment of Lupus Nephritis (LN): From Mechanism of Action to Clinical Perspectives - Bystros, Aleksandra Natalia; Borychowska, Emilia; Marszałek, Dominika; Gwóźdź, Karolina; Mierzejewska, Zofia Aneta; Ocimek, Aleksandra; Drozdowska, Marta; Kurzątkowska, Klaudia; Czudowska, Michalina; Zawadzka, Magdalena (Journal of Education, Health and Sport, 2026)
Background: Lupus nephritis (LN) is one of the most severe and prognostically unfavourable organ complications of systemic lupus erythematosus, which significantly affects patient morbidity and mortality. Despite advances in immunosuppressive therapy, some patients do not achieve sustained renal remission, indicating a need for targeted treatment. Increasing evidence points to the important role of type I interferon signalling in the pathogenesis of SLE and LN. Aim: This review analyses current data on the mechanism of action, clinical efficacy and safety profile of anifrolumab and evaluates its potential role in the treatment of lupus nephritis. Materials and Methods: A narrative literature review was conducted using PubMed and Embase databases, including randomized clinical trials, extended studies and international treatment guidelines published up to 2024. Particular attention was paid to the phase II TULIP-LN trial and key studies assessing anifrolumab in systemic lupus erythematosus. Results: Anifrolumab demonstrated a beneficial effect on immune activity and extra- renal manifestations of SLE. In patients with active lupus nephritis, intensified dosing regimens were associated with a higher rate of complete renal response, greater reduction in proteinuria, improvement in estimated glomerular filtration rate, and more effective glucocorticoid tapering compared with placebo. Although the primary endpoint of the TULIP-LN study was not met, secondary and exploratory results suggest potential renal benefits, particularly with intensified dosing. The safety profile was acceptable, with infections, particularly herpes zoster, being the most frequently reported adverse events. Conclusions: Anifrolumab represents a promising targeted treatment for lupus nephritis. Phase II data indicate potential clinical benefits, but its definitive place in therapy requires confirmation in ongoing phase III trials.